The Interplay between PR Messaging and Loyalty in Young Adult Markets: A Study from Medan City - Widjaya, Arifa Dani Anggit; Ramonita, Latifa (LSPR Institute of Communication & Business, 2025)
As public awareness of environmental and social issues grows, consumers increasingly gravitate toward brands that demonstrate a commitment to sustainability and social responsibility. This shift has prompted businesses to launch campaigns that address these concerns, effectively aligning their values with those of their target audiences. Within the beauty industry, The Body Shop’s